PENGARUH KARAKTERISTIK INDIVIDU, MOTIVASI, DAN KELENGKAPAN SARANA PRASARANA TERHADAP KINERJA PEGAWAI KANTOR URUSAN AGAMA DI KOTA SEMARANG - Widya Danasari, Ayu; Suparjo; Sugiyarti, Gita (Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to analyze the influence of intrinsic motivation and transformational leadership on organizational commitment. In addition, this study also aims to analyze the influence of the mediating variable of organizational commitment on the relationship between intrinsic motivation and transformational leadership on organizational citizenship behavior. The population used was all Assistant Managers of Goods at the Education and Culture Office of Demak Regency, Jl. Sultan Trenggono No. 89, Demak, totaling 478 employees. The sample taken was 118 employees. The types of data used were primary and secondary data. The data collection method used was a questionnaire. The analysis technique used was Path Analysis. The results of the study showed that: 1). Intrinsic motivation has a positive and significant effect on organizational commitment. 2). Transformational leadership has a positive and significant effect on organizational commitment. 3). Organizational commitment has a positive and significant effect on organizational citizenship behavior. 4). Intrinsic motivation has a positive and significant effect on organizational citizenship behavior. 5). Transformational leadership has a positive and significant effect on organizational citizenship behavior. 6). Intrinsic motivation has an effect on organizational citizenship behavior with organizational commitment as an intervening variable. 7). Transformational leadership influences organizational citizenship behavior with organizational commitment as an intervening variable.